Предмет: Алгебра,
автор: Аноним
Упростите
( tg(180° - а)*cos(180° - а)*tg(90° - а) ) / ( sin(90° + а)*ctg(90° - а)*tg(90° + а) )
Ответы
Автор ответа:
0
( tg(180° - а)*cos(180° - а)*tg(90° - а) ) / ( sin(90° + а)*ctg(90° - а)*tg(90° + а) ) = ( sin(180° - а)*tg(90° - а) ) / ( sin(90° + а)*ctg(90° - а)*tg(90° + а) ) =
( sin(а)*ctg(а) ) / ( (cos(а))*tg(а)*(-ctg( а) )) = (cos(а))/(-cos(а)) = -1
( sin(а)*ctg(а) ) / ( (cos(а))*tg(а)*(-ctg( а) )) = (cos(а))/(-cos(а)) = -1
Автор ответа:
0
sin(90° + а) = cos(а) а не sin(90° + а) = -cos(а)
Автор ответа:
0
ошибся, простите, но это только знак изменило)
Автор ответа:
0
все равно это ошибка!
Автор ответа:
0
Приложения:
Похожие вопросы
Предмет: Русский язык,
автор: jagajaga109
Предмет: Математика,
автор: katernukmasa
Предмет: Геометрия,
автор: beluhaivan732
Предмет: Математика,
автор: gh56yuij
Предмет: Математика,
автор: Oksamalce